Harry Potter and the Order of the Phoenix [compact disc, unabridged] - Rowling, J. K. (Rowling, J. K. Year ... at Hogwarts, 2003)
Harry Potter, now a fifth-year student at Hogwarts School of Witchcraft and Wizardry, struggles with a threatening teacher, problematic house elf, the dread of upcoming final exams, and haunting dreams that hint toward his mysterious past.